2009
DOI: 10.1889/jsid17.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐field‐driven LC lens for 3‐D/2‐D autostereoscopic display

Abstract: Abstract— The use of an electric‐field‐driven liquid‐crystal (ELC) lens cell for switching between a 3‐D and 2‐D display is proposed. Due to the phase retardation of the non‐uniform LC directors, an ELC lens functions the same as a geometric lens. The parameters of an ELC for 3‐D applications are optimized through the simulation of the electrode configuration and voltage levels. A prototype was made where the ELC lens is placed in front of a liquid‐crystal display (LCD) 15 in. on the diagonal with a 99‐μm subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…These 3D applications are based on 3D technologies requiring a special eyeglass. After the commercialization of 3D using the special eyeglass, research on autostereoscopic 3D is under way to remove the discomfort of wearing special eyeglass …”
Section: Introductionmentioning
confidence: 99%
“…These 3D applications are based on 3D technologies requiring a special eyeglass. After the commercialization of 3D using the special eyeglass, research on autostereoscopic 3D is under way to remove the discomfort of wearing special eyeglass …”
Section: Introductionmentioning
confidence: 99%
“…Auto‐stereoscopic multi‐view 3D is a 3D technology with which the user can perceive the stereoscopic image without special eyeglasses as reported in multiple studies . Some studies reported various evaluation and measurement methods for 3D …”
Section: Introductionmentioning
confidence: 99%
“…For a PC application, the position of user is decided, and there is no need to rotate the screen. In this case, it is proposed that the voltages of LC GRIN lens are optimized in mainly narrow viewing angle region . The LC GRIN lens has a simple structure that consists of the lens electrode and the LC layer, and therefore, it is easy to manufacture .…”
Section: Introductionmentioning
confidence: 99%